AN EVALUATION OF THE OLBA NYMPHAEUM AND ITS COINS (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2026)
The Nymphaeum of Olba is located northeast of the theatre building and northwest of the Olba Acropolis, which has a sheltered appearance. The studies conducted in Olba revealed how important water is for the city and indicated that various systems were built to meet this need. This study investigates 45 coins unearthed during the 2023 and 2024 excavations of the Olba Nymphaeum. It also presents the catalog and archeological and numismatic analyses of the coins in question. Furthermore, new architectural findings related to the building were interpreted in relation to the coins. The sculptural artifacts, figured sarcophagus fragments, various architectural plastic stone elements from the building's decoration, and glass and ceramic finds recovered during the Nymphaeum excavations indicate that the structure experienced multiple phases of use. The coins analyzed in this study play a pivotal role in corroborating the different phases of the usage of the Nymphaeum.